The Impact of Digital Transformation in Enhancing Operational Performance: An Applied Study in the Kirkuk Electricity Distribution Branch - Marwan Fawzi Takriti; Ghalia Nassreddine; Joumana Younis; Tamima ElHassan (Journal of Techniques)
Digital transformation is the procedure that integrates recent technologies in organizations to push essential change, improve efficiency, and facilitate work for employees. This paper studies the impact of digital transformation on the operational performance of the Kirkuk Electricity Distribution Branch. Four dimensions of digital transformation will be considered: infrastructure, skills, environment, and digital technology. A descriptive analytical methodology was adopted to examine this impact. A questionnaire of 27 questions was built and distributed to the Kirkuk Electricity Distribution Branch employees. The answers from a convenience sample of 328 male and female employees were collected. These answers were examined using SPSS software and statically tools. The result shows a significant impact of the digital transformation on the operational performance of the Kirkuk Electricity Distribution Branch.